The Pístis Christu͂ Debate and its Recent Developments - McFadden, Kevin W. (Reformed theological review, 2023)
After introducing the πίστις Χριστοῦ debate, this article attempts to explain a paradigm shift that has led to the current debate. It then summarizes some recent developments in the subjective genitive view and some recent developments in the objective genitive view. It also introduces readers to a recently articulated "third view" of πίστις Χριστοῦ. Finally, it offers the author's view of the question in conversation with some of the scholars mentioned in the article.